A Comparison of Individual and Group Behavior in a Competition with Cheating Opportunities - Astrid Dannenberg; Elina Khachatryan (Philipps-University Marburg, School of Business and Economics, 2020)
While it is well established that individuals and groups make different economic decisions, the reasons for the behavioral differences are still not fully understood. We experimentally compare individual and group behavior in a competitive setting where cheating can be used to outperform the competitor. Our design allows us to exogenously control for the type of the decision maker, the type of the competitor, and expectations about the competitor's performance. The results show that there is much more cheating in inter-group competition than inter-individual competition which is in line with findings from other interactive games. We show furthermore that this difference is not caused by a higher propensity to cheat of groups per se, but instead by expectations about the competitor. Once we control for the type of the competitor and the decision makers' expectations, we no longer find differences between individuals and groups.
Keywords: C91; D63; H26; 330; individual behavior; group behavior; lying; honesty; competition